Comprehensive N-glycosylation mapping of envelope glycoprotein from tick-borne encephalitis virus grown in human and tick cells - Lattová, Erika; Straková, Petra; Pokorná-Formanová, Petra; Grubhoffer, Libor; Bell-Sakyi, Lesley; Zdráhal, Zbyněk; Palus, Martin; Ruzek, Daniel (Scientific reports, 2020)
Tick-borne encephalitis virus (TBEV) is the causative agent of severe human neuroinfections that most commonly occur after a tick bite. N -Glycosylation of the TBEV envelope (E) glycoprotein is critical for virus egress in mammalian cells, but not in tick cells. In addition, glycans have been reported to mask specific antigenic sites from recognition by neutralizing antibodies. In this regard, the main purpose of our study was to investigate the profile of N -glycans linked to the E protein of TBEV when grown in human neuronal cells and compare it to the profile of virus grown in tick cells. Mass spectrometric analysis revealed significant differences in these profiles. High-mannose glycan with five mannose residues ( Man 5 GlcNAc 2 ), a complex biantennary galactosylated structure with core fucose ( Gal 2 GlcNAc 2 Man 3 GlcNAc 2 Fuc ), and a group of hybrid glycans with the composition Gal 0-1 GlcNAc 1 Man 3-5 GlcNAc 2 Fuc 0-1 were confirmed as the main asparagine-linked oligosaccharides on the surface of TBEV derived from human neuronal cells. The observed pattern was supported by examination of the glycopeptides, providing additional information about the glycosylation site in the E protein. In contrast, the profile of TBEV grown in tick cells showed that paucimannose ( Man 3-4 GlcNAc 2 Fuc 0-1 ) and high-mannose structures with five and six mannoses ( Man 5-6 GlcNAc 2 ) were major glycans on the viral surface. The reported results complement existing crystallography and cryoelectron tomography data on the E protein structure and could be instrumental for designing carbohydrate-binding antiviral agents active against TBEV.